2013
DOI: 10.4236/ojg.2013.32014
|View full text |Cite
|
Sign up to set email alerts
|

Linking of Environmental and Health Indicators by Neural Networks: Case of Breast Cancer Mortality, Slovak Republic

Abstract: This study deals with the analysis of relationship between 67 environmental indicators in geological environment and breast cancer mortality in Slovakia. Primary data comprises a database of 67 environmental indicators for groundwater and soils as a mean value for every Slovak municipality and the data on relative mortality from breast cancer for Slovak municipalities (about 2900) collected for the period of 22 years. The training neural network was used as a mathematical model for data analysis. The top 200 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Environmental indicators (EI) represent chemical elements, chemical compounds, and chemical parameters that are analyzed, measured, and monitored in the environment, which can affect biota or humans [31]. In this work we evaluated 34 EI, mainly inorganic components in groundwater including all common macroelements, trace elements, and basic parameters of natural radioactivity.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental indicators (EI) represent chemical elements, chemical compounds, and chemical parameters that are analyzed, measured, and monitored in the environment, which can affect biota or humans [31]. In this work we evaluated 34 EI, mainly inorganic components in groundwater including all common macroelements, trace elements, and basic parameters of natural radioactivity.…”
Section: Methodsmentioning
confidence: 99%
“…The numbers of residents in municipalities were not random. It is clear from our previous studies [ 29 , 30 ] that small municipalities below 100 residents often showed unbalanced health indicators (small number error). On the other hand, large municipalities (towns) with ≥10,000 residents are often supplied with drinking water from several sources.…”
Section: Methodsmentioning
confidence: 91%
“…We also wanted to avoid the fact that when 4–5 municipalities with >10,000 residents were selected, the necessary variability of health indicators could not be obtained. Municipalities with 500–5000 residents showed the most balanced health indicators and were most closely connected with the environment [ 29 , 30 ]. The selected municipalities are of rural character with similar socio-economic characteristics and other major determinants of health, such as lifestyle, quality and availability of health care [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some districts, this may be related to higher levels of standardized death rates of breast and prostate cancer. Among other things, some districts in Slovakia (e.g., Spišská Nová Ves, Levice, Rimavská Sobota, Bardejov, and others) belong to districts that are burdened with so-called old waste-disposal sites, as well as sites abandoned by their former mainly agricultural, but also industrial, plants that will have to be dismantled in order to avoid further pollution of the soil and groundwater, and, eventually, related health risks [ 60 ]. The map outputs imply a range of information, related to both content and spatial aspects of the regional differences in the standardized death rate of breast and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%